MODEL PENCEGAHAN KONFLIK ANTARUMAT BERAGAMA BERBASIS KEGIATAN MASYARAKAT - Engkizar Engkizar; Soni Kaputra; Mutathahirin Mutathahirin; Syafrimen Syafril; Zainul Arifin; Munawir Kamaluddin (Harmoni, 2022)
Prevention of inter-religious conflict based on community activities offers a new reality for the advancement of living together in religious pluralism because there is a dynamic process in religious understanding and its application. This study aims to look at the prevention model of inter-religious conflict based on community activities. The research was carried out using a qualitative approach (multi-case single-site exploratory case study). Primary data was dug through in-depth interviews with 12 sources with details of 3 Muslims, 2 Catholics, 2 Protestants, 2 Hindus, 3 Buddhists from various regions in Indonesia using the Snowballing technique. Secondary data was extracted through literature analysis of various books, religious scriptures, and scientific articles related to this research. Data were analyzed qualitatively (thematically) with the help of NVIVO 12 software. Overall, the research findings found four main themes of the community activity-based inter-religious conflict prevention model. The four themes are (i) forming a space for dialogue between religious leaders, (ii) real community work through social activities, (iii) ties of cooperation traditions, (iv) support from the community and religious leaders. The results of this study are discussed with various theories and the results of previous research and can be used as a reference for creating peace, harmony, tranquility, harmony, and mutual respect for the principle of togetherness in a pluralistic society